2020
DOI: 10.1108/cg-11-2019-0366
|View full text |Cite
|
Sign up to set email alerts
|

Successful private investor activism in an emerging market

Abstract: Purpose Institutional investors in emerging markets are increasingly under pressure to integrate environmental, social and corporate governance considerations into their investment analyses and ownership practices. Old Mutual Investment Group (OMIG) is a South African-based institutional investor that has long been regarded as a pioneer in responsible investing. The purpose of this study was to examine the nature and effectiveness of OMIG's private shareholder activism endeavours over the period 1 January 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Viviers and Mans-Kemp explored its impact on the performance of corporate governance from the perspective of institutional investors through empirical means. They all concluded that the existence of institutional investors can effectively improve the company's performance [ 6 ]. Rey et al believed that the performance of listed companies with institutional investors is significantly higher than that without institutional investors, and the information disclosure level of listed companies with institutional investors is also significantly higher than that without institutional investors [ 7 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Viviers and Mans-Kemp explored its impact on the performance of corporate governance from the perspective of institutional investors through empirical means. They all concluded that the existence of institutional investors can effectively improve the company's performance [ 6 ]. Rey et al believed that the performance of listed companies with institutional investors is significantly higher than that without institutional investors, and the information disclosure level of listed companies with institutional investors is also significantly higher than that without institutional investors [ 7 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the activism hypothesis, institutional directors encourage management to invest in risky long-term projects to improve productivity and increase the financial institution's effectiveness (Jensen and Meckling, 1976). Institutional directors have the expertise, resources and a better understanding of the sector characteristics compared to the other directors (Hakimi et al, 2018;Viviers and Mans-Kemp, 2020). Jensen (1993) and Naveed and Abdin (2020) add that institutional administrators are more independent and can control management to reduce information asymmetry and decrease agency problems.…”
Section: Institutional Directorsmentioning
confidence: 99%
“…The board diversity represents 8.5% of the total corporate governance topics of the studies published in the journal of Corporate Governance (Bingley) , and this topic was included in the studies in Bhat et al (2020), Elmagrhi et al (2018), Fernández-Temprano and Tejerina-Gaite, (2020), Kyaw et al (2017) and Loukil et al (2019). The emerging market context has also received a considerable attention in several studies on corporate governance, representing 6.80% of the total topics (Agnihotri and Bhattacharya, 2015; Lourenço et al , 2018; Viviers and Mans-Kemp, 2021; Agyei-Mensah, 2016; Fahad and Busru, 2020; Younas et al , 2021; Nobanee and Ellili, 2022).…”
Section: Results Of Bibliometric and Content Analysesmentioning
confidence: 99%
“…There is a need to analyze the impact of other corporate governance mechanisms on investment efficiency. This will help companies to optimally manage their corporate governance framework and enhance their investment strategies. Corporate governance across countries: As indicated in Table 4, most corporate governance studies focused on emerging markets (Agnihotri and Bhattacharya, 2015; Lourenço et al , 2018; Viviers and Mans-Kemp, 2021; Agyei-Mensah, 2016; Fahad and Busru, 2020; Younas et al , 2021; Nobanee and Ellili, 2022). Cross-country corporate governance studies should be conducted to provide valuable insights into this topic by considering the differences between the institutional contexts. Corporate governance and dividend policy : The dividend policy is one of the most important financial decisions of a company and has a direct impact on shareholders’ wealth.…”
Section: Directions For Future Corporate Governance Research Topicsmentioning
confidence: 99%
See 1 more Smart Citation